Beyond Financial Metrics: A Systematic and Bibliometric Review of Hotel Business Performance - Carlos Sampaio; Mónica Régio; João Renato Sebastião (Administrative Sciences)
Hotel business performance has been traditionally measured through financial metrics. Nevertheless, recent research emphasizes the increasing relevance of non-financial metrics such as sustainability, stakeholder perceptions, and strategic management practices. This study assesses the evolution of the measurement of hotel business performance within the scientific literature to identify trends and theoretical frameworks that shape performance measurement. The methodological approach employs qualitative and quantitative analysis, through a bibliometric analysis, to track the development of performance metrics in the field. The findings suggest that the assessment of hotels’ business performance shifted from the use of pure financial metrics to a more integrated perspective, including factors such as social responsibility, customer satisfaction, and sustainability. Furthermore, external factors such as economic crises could also significantly influence hotel performance. Future research should further explore the role of technology and regional variations in shaping hotel business success.